TEMPLES ALONG THE VITASTA - Singh, Jai Karan; Mondal, Munmun (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Vitasta the ancient name of river Jhelum flowing through the valley of Kashmir in the Union Territory of Jammu and Kashmir (J&K) is one of the important rivers mentioned in the Rig Veda. As per Nilamata Purana, the river emerges from the Nilnag which is called by the name Verinag in present context. Jhelum may be regarded as the lifeline of Kashmir valley, and it holds true in present as well as ancient context. The river has many important monuments right from its emergence up to its merger with Chenab in Pakistan. Most importantly, it may be regarded as cradle for the birth of Kashmiri Temple Architecture found in the valley which has found its distinct place in Nagara style of architecture in Temple architecture. The paper is presently focusing only on the Brahmanical temples built along the banks of the river and in its close periphery. More importantly from an architectural point of view, it will highlight the importance of river Jhelum (Vitasta) and its significance in the emergence of unique temple architecture.